The bucket list - Mohlin, Peter; Nyström, Peter, (Crime fiction writer) (Mohlin, Peter. Agent John Adderley novel., 2021)
With a price on his head, undercover FBI Agent John Adderley, after surviving a brutal attack, investigates a high-profile cold case involving a young heiress that he is determined to solve while hiding until he can testify against the drug cartel he infiltrated back in the States.